Organizational Transparency: Conceptualizations, Conditions, and Consequences. Issue 2 (February 2019) - Albu, Oana Brindusa; Flyverbom, Mikkel
Transparency is an increasingly prominent area of research that offers valuable insights for organizational studies. However, conceptualizations of transparency are rarely subject to critical scrutiny and thus their relevance remains unclear. In most accounts, transparency is associated with the sharing of information and the perceived quality of the information shared. This narrow focus on information and quality, however, overlooks the dynamics of organizational transparency. To provide a more structured conceptualization of organizational transparency, this article unpacks the assumptions that shape the extant literature, with a focus on three dimensions: conceptualizations, conditions, and consequences. The contribution of the study is twofold: (a) On a conceptual level, we provide a framework that articulates two paradigmatic positions underpinning discussions of transparency, verifiability approaches and performativity approaches; (b) on an analytical level, we suggest a novel future research agenda for studying organizational transparency that pays attention to its dynamics, paradoxes, and performative characteristics.